Perbedaan Kepuasan Kerja dan Motivasi Kerja antara Pegawai Permu BULOG yang Pernah Mengalami Rotasi Kerja dan yang Belum Pernah Mengalami Rotasi Kerja - , Liesa Pratiwi, SH. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This paper studies differences in job satisfaction and work motivation between employees with different characteristics, to job rotation in Perum BULOG. A test on 300 employees randomly selected from its branches, showed that job rotation is related to job satisfaction and work motivation. Also, job rotation may be a proactive way to enhance positive affect and perceptions of skill acquisition and other benefits both for employee and employer. Organizations should apply job rotation as means to address issues related to employees' job monotony, boredom and fatigue as a result of job specialization. Only by doing so organizations could release the maximum potential from human resources management systems.